2009
DOI: 10.1007/s12011-009-8443-5
|View full text |Cite
|
Sign up to set email alerts
|

Nail Antioxidant Trace Elements Are Inversely Associated with Inflammatory Markers in Healthy Young Adults

Abstract: Antioxidant intake may be linked to a reduction of the chronic low-grade inflammatory state related to obesity and several accompanying disorders such as insulin resistance, cardiovascular diseases, and metabolic syndrome. So, the aim of this study was to evaluate the potential associations between nail trace elements and several indicators in healthy young adults, emphasizing on the putative effect of antioxidant trace element intake on inflammation-related marker concentrations. This study enrolled 149 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Selenium is an essential antioxidant mineral, whereas its increased consumption has been inversely associated with pro-inflammatory markers [34,35] as well as with lower hypercholesterolemia [36,37] and lower LDL susceptibility to oxidation [38]. In addition, increased nail selenium levels also have been related to lower pro-inflammatory marker concentrations, such as complement C3 factor, asymmetric dimethylarginine, and interleukin-18 in young healthy adults [13,14,19]. According to previous and onset findings, it could speculate an inverse relationship between dietary selenium intake and the oxidation of LDL-c.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selenium is an essential antioxidant mineral, whereas its increased consumption has been inversely associated with pro-inflammatory markers [34,35] as well as with lower hypercholesterolemia [36,37] and lower LDL susceptibility to oxidation [38]. In addition, increased nail selenium levels also have been related to lower pro-inflammatory marker concentrations, such as complement C3 factor, asymmetric dimethylarginine, and interleukin-18 in young healthy adults [13,14,19]. According to previous and onset findings, it could speculate an inverse relationship between dietary selenium intake and the oxidation of LDL-c.…”
Section: Discussionmentioning
confidence: 99%
“…Fingernail and toenail samples were treated with sub-boiling nitric acid in a high-pressure teflon digestion vessel using a microwave digestion system (Ethos Plus, Millestone, Sorisole, Italy). Selenium (ng/g of nail), copper and zinc (μg/g of nail) concentrations were measured by a Perkin Elmer Analyst 800 atomic absorption spectrometer (Norwalk, CT, USA) as previously described [28,29]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed a possible role for Se intake in the modulation of C3; its assessment may be an early marker of the MetS manifestations. [ 37 ] Nail content on some trace elements related to antioxidant defense mechanisms seems to be associated with several inflammation-related markers linked to chronic diseases in apparently healthy young adults,[ 38 ] negative and significant associations between MetS and Se intake. [ 39 ] ADMA seems to be related with Se status and several anthropometric and biochemical measurements linked to MetS in apparently healthy young adults.…”
Section: Resultsmentioning
confidence: 99%
“…3 The relationship between antioxidant trace elements measured in the nail and the blood inflammatory markers' concentrations has been studied before. 4 Therefore, antioxidant intake may be linked to a reduction of the chronic low-grade inflammatory state seen in different metabolic syndromes. 4 In a recent study, Wang and colleagues 5 suggested that multivitamin and mineral supplementation, for example, zinc, could have blood pressure lowering effect and could reduce serum C-reactive protein (CRP) in the women studied.…”
Section: Dear Sirmentioning
confidence: 99%